ILMU ADALAH KEKUASAAN PERAN DAN IMPLIKASINYA (TINJAUAN EPISTIMOLOGIS) - Ni Ketut Tri Srilaksmi (PARIKSA: Jurnal Hukum Agama Hindu, 2019)
Analysis of Why Religio matters, when the world has entered the modern era, there is chaos and killing in religion. This is due to the authoritarian nature of the ruling. This was marked by political and scientific power (scientism) which was combined into a modern ideology, secularism. Science in the framework of secularism turned into scientism, which was based on the scientific method, which replaced the position of revelation as a new way to find the path to more true science.Scientism is an ideology built on the assumption that science can provide knowledge about everything we want to know, which makes scientism a secular religion, while technology is an indicator of the development of science. Technology is the primary tool for the progress of humanity. The impact of this is the marginalization of existing religions.This makes it easy to get power when we can predict the future by utilizing knowledge and science. So from the discussion above, this jurnal will identify the notion of science, and, the difference between science and expertise. Also discussed will be the science of power itself and its implications.